THE EFFECTIVENESS OF PARALLEL WRITING TO IMPROVE STUDENTS WRITING NARRATIVE TEXT - Cep Bahrul Ulum; surya darmawan (IKIP Siliwangi, 2018)
English as a global language in all over the world seems to be a priority for people to learn. It is because as social creatures, people absolutely need to communicate in their everyday life in order to socialize or to express their thought, feeling, understanding, opinion, critic, and everything that they want to share to others. English becomes language that should be learn by all students in Indonesia. It has four language skills to be mastered; listening, speaking, reading and writing. However, during the time, most of students have difficulties in mastering writing skill. Those difficulties come because the process of writing requires an entirely different set of competencies and is fundamentally different from speaking (Douglas & Heekyeong, 2015). Therefore, regarding to those difficulties, this research offered one of the language teaching techniques which hopefully can be applied as one of alternatives way in teaching to improve students’ writing skill especially in writing narrative text. Moreover, the writer comes up with a research entitled; The Effectiveness of Parallel Writing Technique to Improve Students Writing Skill in Narrative Text. This study was conducted at one of junior high school in West Bandung involving 30 students as the sample. Then, by using pre-test as post-test as the main instruments calculated with t-test statistical computation, it can be seen that there is significant improvement coming from the students after they got parallel writing technique. Therefore, it is hoped that it can be beneficial for the improvement of writing skill. Keywords: Parallel Technique, Students Writing, Narrative Text.